Plasma thiol levels are associated with disease severity in nonsegmental vitiligo - Gulsen Akoglu; Salim Neselioglu; Eda Karaismailoglu; Akin Aktas; Ozcan Erel (Wolters Kluwer Medknow Publications, 2018)
Background: Vitiligo is a depigmenting cutaneous disorder with complex pathogenesis. Thiol compounds are well-known organic structures that play a major role in melanogenesis. Aim: The aim of this study was to determine the association between plasma thiol level and disease severity in patients with nonsegmental vitiligo. Methods: A total of 73 patients with nonsegmental vitiligo (57 generalized and 16 localized type) and age- and sex-matched 69 healthy controls were enrolled in the study. Plasma levels of native thiols, disulfides, and total thiols were measured by a novel and automated assay. Disease severity of vitiligo was assessed with Vitiligo Area Scoring Index (VASI) score. The extent, stage, and spread of vitiligo of patients were evaluated according to the Vitiligo European Task Force (VETF) system. Results: The native and total thiol levels of vitiligo patients were higher than those of healthy control group (P≤0.001 and 0.001, respectively). The median VASI score of patients was 0.7 (0.02-28.30). Univariate analyses showed that plasma native thiol levels, VETF spread score, disease duration, and vitiligo type significantly correlated with VASI scores (r=0.237, P=0.043; r=0.458, P<0.001; and P<0.001, respectively). Stepwise multivariate analysis revealed that disease duration (β=0.017; P=0.005) and spread score (β=1.301; P=0.001) were found statistically significant as independent factors on VASI score. Conclusion: Although plasma native thiol level significantly correlated with VASI scores of patients, it is not a predictive factor for vitiligo severity.